Fitness to practise for doctors and medical students with mental issues in Malaysia / Muhammad Darwiis Abdullah … [et al.] - Abdullah, Muhammad Darwiis; Ahmad Fuad, Aiman Faiz; Rahman, Hafiz Ilmie; Tan, Mark Kiak Min (Universiti Teknologi MARA Cawangan Selangor, 2019)
Mental illness is expected to become the second biggest health problem affecting Malaysians by 2020. Doctors and medical students are more prone to mental illness compared to the general population. However, they are often reluctant to and resist seeking help because of stigma and a (strong) sense of shame. This can lead to detrimental consequences for themselves and their patients. That said, a doctor with a mental illness receiving appropriate treatment and who is in a stable condition may still be permitted to practise provided patient safety is not compromised. Determining this is a key responsibility of a healthcare regulator like the Malaysian Medical Council (MMC). Using some prominent cases to illustrate this point, this article reviews the MMC guideline on ‘Managing Impaired Registered Medical Practitioners’. In the absence of similar local guidelines for medical students, we also allude to the UK General Medical Council’s guideline on ‘Supporting Medical Students with Mental Health Conditions’. The article recommends that doctors and medical students with mental illness should seek help; outlines a number of factors to consider in deciding whether a doctor should continue practising; and explores alternative career paths in instances where they should not. The article concludes that appropriate support goes a long way for doctors and medical students who grapple with mental health issues in that there is hope and a way through a seemingly devastating situation.